(untitled) (Research, Society and Development, 2024)
The use of resistant maize genotypes may reduce the damage caused by Sitophilus zeamais (Coleoptera: Curculionidae). In this context, the objective of this work was to evaluate the resistance of three maize genotypes to attack by S. zeamais. On the attractiveness test the genotypes were made available to S. zeamais, and after 24h the insects in each genotype were counted. Oviposition was evaluated by releasing 30 adults on 10 grains of each genotype, the postures being registered after 72h. On the development test, 20 adults were confined in cages with 40g of each genotype. After 30 days the insects were removed, and the cages were surveyed daily during 60 days for registering and removal of emerged adults, evaluating the duration of the immature phase, loss of mass, susceptibility index (SI) and instant growth rate (ri). The genotypes did not influence attractiveness for S. zeamais nor oviposition, with popcorn and Bt maize having an average of six postures, while the landrace maize had an average of five postures. The duration of larval phase was 10% longer on popcorn maize, besides the smallest ri (3,43), followed by the landrace maize (4,09) and Bt (5,09). The popcorn maize had the smallest loss of weight (2,96%), with a difference greater than 20% when compared to the landrace maize (4,18%) and Bt (3,82%). The popcorn maize was the most resistant to S. zeamais, presenting possible antibiosis.